Optimization Of Time-Driven Scheduling Technique For Serverless Cloud Computing - et. al., Dr. S. Rama krishna, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Serverless Computing has become more common by providing lower costs, better elasticity and enhanced usability. Taken as a consequence that resource restrained infrastructure requires efficient low-latent calculations, it also becomes a common execution model for edge computing. However, the cloud mitigation of hyper scale in the cold start server is not scaled to small 10-100kW edge sites, resulting in weak threshold latencies for edge deployments of existing VMs and containers. This is particularly acute since latency requirements are expected to range from micro seconds to seconds in future edge computing workloads. SledgeEDF is the first time that the serverless execution paradigm applies conventional real- time admittance management systems and time-driven scheduling techniques.